Salud e interculturalidad: saberes, asimetrías y lugares comunes. - Gil, Gastón Julián; Incaurgarat, María Florencia (Brazilian Journal of Occupational Therapy / Cadernos Brasileiros de Terapia Ocupacional, 2022)
Whether as an effective theoretical instrument, a discussion cliché, or a moral appeal, the analysis of interculturality as a constitutive part of the health-disease-care process is increasingly part of the daily concerns of health professionals. However, this apparent and growing consensus is not always accompanied by effective use of socio-anthropological approaches that overcome the limitations of biomedical knowledge or the use of common sense. This article analyzes some of those frequent uses of the "cultural" that fail to propose comprehensive and overcoming approaches. For doing so, some ethnographic cases are used to show the relevance of having solid theoretical and methodological tools to minimize an "asymmetric" use of the notion of culture. This implies that "the cultural" tends to be seen as an exoticism or even an irrationality that only deserves a careful analysis when patients belong to groups and collectives that contrast markedly with our supposed normality. On the contrary, it tries to show that "the cultural" is constitutive of the daily normality of the people who use the health system.